What Psychology Can Contribute to Contemporary Teacher Education: Basic Concepts and Exemplary Implementations - Stephan Dutke; Manfred Holodynski; Elmar Souvignier (Charles University, 2019)
Abstract We describe basic concepts of contemporary teacher education from a psychological perspective, typified with examples from teacher education programs run at the University of Münster, Germany. After describing the context of teacher education in Germany, criteria are discussed which guide the selection of psychological contents to be included into teacher education curricula. Furthermore, three curriculum components are discussed that help to adopt a psychological perspective on instruction at school. Classroom videos reduce the distance between psychological knowledge suitable to guide teacher behaviour and examples of how teachers actually behave during class. Students' small-scale classroom research projects bridge the gap between theory and practice, and curriculum components focussing on individual differences help to raise awareness for diagnostics, individual aid, and inclusion. Finally, psychology's role in teacher education is discussed with regard to relevant content knowledge and methodological knowledge teacher education curricula might benefit from.   Key words: teacher education, video-based instruction, evidence-based teaching, inclusion